A low-power column-parallel cyclic ADC for CMOS image sensor with capacitance and current scaling. (November 2020) - Zhu, Jianian; Xu, Jiangtao; Nie, Kaiming
Abstract: This paper presents a power-optimized column-parallel cyclic ADC for CMOS image sensor readout circuits. By separating the capacitor and bias current source and floating them in the circuit, the multiplying digital-to-analog converter (MDAC)'s capacitive load and bias current can be significantly decreased during least signiﬁcant bit (LSB) quantization, which allows the ADC to reduce power consumption while maintaining a constant conversion rate. The residual quantization characteristic of MDAC makes the input-referred noise produced in LSB quantization relatively small, so the additional noise generated by capacitance scaling can be compensated by increasing the capacitance load of the most signiﬁcant bit (MSB). A 14-bit two-stage column-parallel cyclic ADC is designed using 0.13-μm technology. The simulation results show that the effective-number-of-bit (ENOB) is 13.54 bit under 0.96-μs sampling rate, and the power consumption of each column is 631 μW. Compared with the traditional structure, the power consumption of ADC is reduced by 35.1%, while the performance remains unchanged.